Non-invasive Prenatal Test - A Pilot Pan-India Experience of an Indian Laboratory - Sinkar, Prachi; Iyer, Sandhya; Kallathiyan, Kallathikumar (Asian Journal of Biological and Life Sciences, 2020)
Background:Serum-based tests are considered to be a very affordable screening option for pregnant women. The non-invasive prenatal test (NIPT), among prenatal screening for chromosomal aneuploidies has a sensitivity of >99%. The focus of this report is to present an overview of NIPT outcome from samples tested in our national laboratory over a period of six months.Materials and Methods:NIPT was done by whole genome shot gun sequencing and a total of 513 pregnant women were tested in our laboratory. The samples were analyzed for reporting on risk of trisomy 21, 18 and 13 as well as sex chromosome aneuploidies.Results:A total of 513 blood samples were received for NIPT testing and 9.3% were cancelled at the pre-analytical stage. Frequency of routine and IVF pregnancies was detected to be 83% and 12% respectively. Frequency of high risk including trisomy 21, trisomy 18 and sex chromosome aneuploidies was detected to be at 3.0% respectively. A total of 7% of cases which were reported high risk by serum screening were detected to be low risk by NIPT.Conclusion:NIPT is an efficient aneuploidy screening tool as it studies fetal DNA and our analysis indicates that the same can be beneficial in screening for fetal chromosomal risk with high sensitivity to identify cases which need confirmatory tests.
Keywords: Cell free DNA; Next-Generation Sequencing; Non-Invasive Prenatal Testing; Pregnancy; Screening